2011
DOI: 10.4067/s0718-58392011000200017
|View full text |Cite
|
Sign up to set email alerts
|

Improving meat quality through natural antioxidants

Abstract: Nowadays, consumers are demanding more natural foods, obliging the industry to include natural antioxidants in foods. Natural antioxidants have been used instead of synthetic antioxidants to retard lipid oxidation in foods to improve their quality and nutritional value. This review discusses some aspects of recent research on antioxidant activity of plant extracts and natural compounds to improve meat quality. Many herbs, spices, and their extracts have been reported as having high antioxidant capacity, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
133
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(156 citation statements)
references
References 65 publications
7
133
0
6
Order By: Relevance
“…Nevertheless, our findings did not support those of Fernandez-Lopez et al (2005), who claimed that using natural extracts applied to beef meatballs during storage had significant advantages. Previous studies have shown that the presence of natural antioxidants could retard the formation of metmyoglobin and have highly suppressive effects and decrease L* or increase a* values (Fernandez-Lopez et al, 2005;Velasco and Williams, 2011). In contrast, Kim et al (2014) suggested that the color of the thigh muscle was not affected by supplementation of broiler diets with increased levels of red ginseng marc.…”
Section: Ph and Meat Colormentioning
confidence: 49%
“…Nevertheless, our findings did not support those of Fernandez-Lopez et al (2005), who claimed that using natural extracts applied to beef meatballs during storage had significant advantages. Previous studies have shown that the presence of natural antioxidants could retard the formation of metmyoglobin and have highly suppressive effects and decrease L* or increase a* values (Fernandez-Lopez et al, 2005;Velasco and Williams, 2011). In contrast, Kim et al (2014) suggested that the color of the thigh muscle was not affected by supplementation of broiler diets with increased levels of red ginseng marc.…”
Section: Ph and Meat Colormentioning
confidence: 49%
“…On meat industry they have been extensively used synthetic antioxidants (SA) such as butylatedhydroxyanisole (BHA), and butylatedhydroxytoluene (BHT) to prevent any oxidative changes (Monahan & Troy, 1997). However, because of the negative impression regarding the use of SA; natural antioxidants (NA) consider the suitable replacement (Velasco & Williams, 2011). Several research studies were reported possible carcinogenic and toxicological effects of the SA used in human foods (Altmann et al, 1986;Kumar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As natural antioxidant, plant extract can donate hydrogen ions to inhibit free radical formation and/or interrupt propagation of autoxidation in muscle food (Falowo, Fayemi, & Muchenje, 2014). As potential preservative agents, plant extract possesses huge bioactive compounds which are capable of disrupting and degrading the cytoplasmic membrane and cell wall of spoilage microorganisms (Kim, Cho, & Han, 2013;Radha Krishnan et al, 2014) and also improve the physicochemical qualities of processed meat products (Shah, Don Bosco, & Mir, 2015;Velasco & Williams, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To deal with these undesirable changes and reduce the use of synthetic preservatives, extracts from plant sources are added to meat and meat products as natural additives (Falowo et al, 2014;Velasco & Williams, 2011). Interestingly, extract from Moringaceae (Moringa oleifera Lam.)…”
Section: Introductionmentioning
confidence: 99%